ANALISIS SURVEI KEPUASAN MASYARAKAT TERHADAP PENYELENGGARAAN PELAYANAN PASANG BARU (STUDI KASUS DI PT. PLN (PERSERO) RAYON SEMARANG TENGAH) - Rochmana, Ulya; Yuniningsih, Tri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Electricity is one of the basic needs of people in Indonesia. PT. PLN (Persero) is one of the State Owned Enterprises (BUMN), which has the task or function to organize the supply of electricity as the needs of the community. New installation service provided by PT. PLN (Persero) Rayon Semarang Tengah are still many shortcomings that can be said to be less good. This research is compiled to analyze the public community satisfaction on the implementation of the new installation services by PT. PLN (Persero) Rayon Semarang Tengah. This research uses descriptive quantitative approach. The theory used is to look at PERMEN PAN and Reformasi Birokrasi No. 16 Tahun 2014 on Societies Satisfaction Survey Implementation of Public Service by referring to the 9 scope of services. Satisfaction Masyararat views of suitability between the level of service performance and the level of interest/ community expectations. Based on study results, the services provided by PT. PLN (Persero) Rayon Semarang Tengah has been good with the performance levels of 2.99 and 3.40 at the level of interest so that the level of conformity obtained is high at 87.87% so it can be said the community is satisfied with the services provided. From 9 scope of services analyzed, there are 2 criteria/ elements that still does not give satisfaction to the community, the first is service procedures with interest rate of 3.47, while the level of performance is still low at 2.85 so the suitability 82.21 and the second is the handling of complaints, suggestions, and recommendataio the performance level still lower that 2.52 while the interest is as high as 3.51 and a low level of concordance is lowest 71.70%.